IMPLEMENTASI PEMBELAJARAN ONLINE BERBASIS EDMODO DALAM SITUASI PANDEMIK COVID-19 UNTUK MATERI KEPENDIDIKAN PADA PRODI PENDIDIKAN SENI PERTUNJUKAN - Ujang Pratama; Galuh Destari Kumala Dewi (Universitas Pendidikan Ganesha, 2020)
The COVID-19 pandemic has brought significant and spontaneous changes to the realm of education, including learning performing arts in higher education. Face-to-face learning in the classroom was replaced by online learning. Teachers need to explore online learning applications to provide learning facilities at home. This paper presents a discussion regarding Edmodo-based online classroom implementation as a tool for distance learning. The implementation has been carried out on performing arts pedagogy courses, namely Curriculum & Instruction, Classroom Management, Instructional Technology, and Art's Learning Evaluation, in performing art education study programs. From the results of implementing the Edmodo, it is known that most students could pass courses based on their final grades. This implementation is an example of setting online design on the subject of other performing arts pedagogy.